Could different TMJ disc positions observed in MRI cause different sounds? Analysis on a group of subjects with ADD with reduction: a pilot study. Issue 4 (October 2014) - Deregibus, A.; Castroflorio, T.; De Giorgi, I.; Burzio, C.; Debernardi, C.
Abstract : Aims: Magnetic resonance imaging (MRI) is the method of choice for examining soft-tissue pathology of the temporomandibular joint (TMJ). MRI shows a high spatial resolution with accuracy for the identification of internal derangement. Tasaki developed a classification system for disc displacement in the TMJ, identifying eight different types of disc displacements in addition to the superior disc position. This study aims to test the ability of electrosonography (ESG) in discriminating different kinds of disc displacement according to the disc position criteria proposed, comparing the ESG results with those obtained by MRI. Methodology: Twenty-seven patients were selected from an initial group of 50 patients with articular disc displacement, selected by means of clinical examinations, according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and who had both MRI and ESG studies performed. For each patient and for each peak in ESG, both in the opening and closing movements, three different parts of the sound were analyzed. The frequency (Hz) and the mean amplitude (μV) of the sounds were calculated in the three analyzed windows. Afterwards, gathering the data for the Tasaki's classes and dividing opening and closing sounds, the number of peaks was calculated, as well as average and standard deviations for both the Hz and µV. Results: The peak frequency shows significant differences between different disc positions during the first and second third of the opening phase and during the first third of the closing phase. The peak amplitude shows significant differences between different disc positions during all of the opening and closing phases. Conclusions: Although limited by sample size, the present study shows the presence of different sounds with different Hzs and μVs associated with different disc positions that were recorded with ESG.